Does hotel management matter to overcoming the COVID-19 crisis? The Spanish case. (February 2022) - Hidalgo, Alberto; Martín-Barroso, David; Nuñez-Serrano, Juan A.; Turrión, Jaime; Velázquez, Francisco J.
Abstract: This paper analyses the influence that the initial actions and strategies pursued by hotel managers have on the recovery of occupancy after a crisis such as the COVID-19 pandemic. To do this, a specific survey is carried out on managers of Spanish hotels. The main findings show that labour actions, especially plans for temporary employment regulations, innovation and differentiation strategies, reorientation to closer markets and obtaining information from official sources as a guarantee of their certainty, are the measures that have a greater impact on the possibilities of recovering hotel activity. In addition, government measures that contribute to the improvement of the financial situation of firms can also play a relevant role in hotel recovery.